GENDER MODERATES ASSOCIATION BETWEEN EMOTIONAL‐BEHAVIORAL PROBLEMS AND TEXT COMPREHENSION IN CHILDREN WITH BOTH READING DIFFICULTIES AND ADHD. Issue 5 (26th March 2017) - Mano, Quintino R.; Jastrowski Mano, Kristen E.; Denton, Carolyn A.; Epstein, Jeffery N.; Tamm, Leanne
Abstract : Evidence suggests that higher order linguistic functioning such as text comprehension is particularly vulnerable to emotional modulation. Gender has been identified as an important moderating variable in emotional expression such that girls tend toward internalizing emotions (e.g., sadness, anxiety) whereas boys tend toward externalizing emotions (e.g., anger, combativeness), which may influence the relationship between emotion and text comprehension. The present study examined whether gender moderates the relationship between emotional‐behavioral problems and text comprehension among children ( n = 187; boys = 115, girls = 72) with both word reading difficulties (RD) and attention‐deficit/hyperactivity disorder (ADHD), a sample widely acknowledged to be at increased risk for developing emotional‐behavioral problems such as anxiety, poor academic self‐concept, and delinquency. A moderated regression analysis tested for the significance of two separate interaction terms (i.e., gender × externalizing problems, gender × internalizing problems) after controlling for gender, IQ, basic reading skills, cognitive‐linguistic processes closely related to reading, attentional problems, internalizing problems, and externalizing problems. Results indicated that gender significantly and uniquely moderates the relationship between emotional‐behavioral problems and text comprehension. Specifically, text comprehension was relatively lower among girls with relatively higher externalizing problems, whereas no such association was observed among boys. These results contribute to our understanding of cognition–emotion interactions within reading development and raise important implications.